DETERMINANTS OF FRANCHISEE SURVIVAL: AN EMPIRICAL STUDY IN MALAYSIA - Nor Hafiza Othman; Nurul Faizah Halim; Nur A’mirah Mohd Yaziz, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2025)
The franchise business model has become one of the most successful business models of the 21st century. However, franchisees often face significant challenges in navigating economic downturns and maintaining profitability. This study aims to identify the key factors that influence business survival in Malaysia. It involved 165 franchise business owners, using purposive sampling to collect data through a questionnaire. The data were analyzed using multiple linear regression with IBM SPSS version 26. The findings indicate that financial resources, value proposition, and government support positively contribute to franchisee survival. Among these factors, government support emerges as the most critical element in ensuring business survival during crises or pandemics. This study makes a significant contribution by integrating the Resource-Based View and Institutional Theory, providing strategies to enhance franchisee resilience. Additionally, it offers a comprehensive framework for evaluating franchisee survival capabilities, yielding valuable insights into the franchising industry. Future research should explore the transformative potential of technology-driven strategies, which could offer valuable solutions for franchisees seeking to adapt and thrive in an increasingly dynamic market.